Pengaruh Online Customer Review Dan Online Customer Rating Terhadap Purchasing Decision Dengan Trust Sebagai Mediasi Pada Produk Skincare Di Shopee - Rustika, Laela; Pambudi, Bambang Setiyo (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
In general, the aim of this research is to determine the direct and indirect influence of online customer reviews and online customer ratings on purchasing decisions with trust as a mediator for skincare products at Shopee. This study uses a quantitative approach. The sampling technique uses a non-probability sampling technique with a purposive sampling method. Then analyzed using path analysis with the help of SmartPLS software. There are seven hypotheses in this research. Based on the results of hypothesis testing, it was found that of the seven hypotheses, three hypotheses were accepted and four hypotheses were rejected. From the results of the analysis that has been carried out, the conclusions in this research can be drawn: (1) online customer reviews do not have a significant effect on purchasing decisions, (2) online customer ratings do not have a significant effect on purchasing decisions, (3) Trust has a significant effect on purchasing decisions, (4) online customer reviews have no significant effect on trust, (5) online customer ratings have a significant effect on trust, (6) online customer reviews have no significant effect on purchasing decisions with trust as mediation, (7) online customer ratings have a significant effect on purchasing decision with trust as mediation.